2018
DOI: 10.1002/2017ja024654
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Wave Height Estimation from GPS‐Derived Ionospheric Data

Abstract: Large underwater earthquakes (Mw>7) can transmit part of their energy to the surrounding ocean through large seafloor motions, generating tsunamis that propagate over long distances. The forcing effect of tsunami waves on the atmosphere generates internal gravity waves that, when they reach the upper atmosphere, produce ionospheric perturbations. These perturbations are frequently observed in the total electron content (TEC) measured by multifrequency Global Navigation Satellite Systems (GNSS) such as GPS, GLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
(88 reference statements)
1
27
0
1
Order By: Relevance
“…Acoustic waves in the atmosphere associated with TIDs are common and can be caused by a variety of sources, including volcanic eruptions [18], earthquakes [19][20][21], tsunamis [22], large storms [5,23], solar flares [23], meteorite impacts [23], interplanetary shocks [24], and human-caused sources such as explosions [25] and rocket launches [26] (see [23,27] for comprehensive lists). There is now compelling evidence that the ionosphere is sufficiently affected by earthquake-related ground motion and tsunami waves, the latter of which can be tracked with TEC [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic waves in the atmosphere associated with TIDs are common and can be caused by a variety of sources, including volcanic eruptions [18], earthquakes [19][20][21], tsunamis [22], large storms [5,23], solar flares [23], meteorite impacts [23], interplanetary shocks [24], and human-caused sources such as explosions [25] and rocket launches [26] (see [23,27] for comprehensive lists). There is now compelling evidence that the ionosphere is sufficiently affected by earthquake-related ground motion and tsunami waves, the latter of which can be tracked with TEC [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…With GNSS TEC observations, researchers have also attempted to retrieve tsunami characteristics, primarily the wave heights, from the tsunami‐induced ionospheric TEC perturbations. The first and only effort was reported by Rakoto et al (), who assumed that the tsunami wave height, tsunami‐induced atmospheric gravity waves, and their respective ionospheric TEC perturbations could be expressed by a normal‐mode summation with momentum tensor and Legendre polynomials defined in Phinney and Burridge (). By using a least‐squares approach, they successfully inverted the GPS‐derived TEC data to tsunami wave heights for three events.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%
“…As the example given by Rakoto et al (), the inversion of the observed ionospheric signatures back to quantitative characteristics of surface disturbances relies on numerical modeling tools that simulate the response of the upper atmosphere to atmospheric acoustic‐gravity waves generated from surface disturbances. However, modeling approaches contain caveats that limit their capability to represent realistic acoustic‐gravity wave propagation.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%
“…Tsunamis also create disturbances in the ionosphere and are being captured by the ever-increasing arrays of GNSS, such as the Global Positioning System (GPS), Globalnaya Navigazionnaya Sputnikovaya Sistema (GLONASS), and, in the future, Galileo (Occhipinti et al, 2018;Rakoto et al, 2018). The ability of tsunamis to excite internal gravity waves in the atmosphere has been recognized since the early seventies (Hines, 1972).…”
Section: Ionospheric Perturbationsmentioning
confidence: 99%